AN ANALYSIS OF THE FIRST LANGUAGE ACQUISITION AT THE TELEGRAPHIC STAGE - Patricia Vamelaa; Farnia Sari (Universitas Bandar Lampung, 2023)
The purpose of this research was to analyze how the first language acquisition can affect students' talking process at the telegraphic stage. The researcher conducted the qualitative methods. The population of this research was the children at the telegraphic stage around 2-2,5 years old. The data from 20 samples are analyzed. The Data describes when the child begins to produce utterances that are longer than two words, these utterances appear to be the hierarchical, constituent structures similar to the syntactic structures found in the sentences produced by adult grammar. The current study investigates the accessibility of a systematic pattern to children learning their first language, and also it is a try to show the effect of the quantity of input on first language acquisition. To these aims, two case studies were carried out on twenty children learning their first language. In-depth observations and video recordings, notes and reports were used to collect the data for this study. The data collected for each child was analyzed separately, and the stages of development were reported for each child accordingly. The findings support the claim that the process of language acquisition depends on an innate language ability which holds that at least some linguistic knowledge exists in humans at birth, and the input that learners receive plays a very important role in the language acquisition since the input activates this innate structure.